Effectiveness of Isometric Handgrip Exercise on Blood Pressure in Hypertensive Patients in Tenajar Lor Village, Kertasemaya District, Indramayu Regency - Riyanto, Riyanto; Kenanga Purbasary, Eleni; Husnaniyah, Dedeh; Gilang Pratama, Satrio (Ann Publisher, 2024)
Uncontrolled hypertension may result in numerous consequences; effective management is essential to regulate blood pressure in hypertensive individuals by both pharmacological and non-pharmacological interventions. Isometric handgrip exercise is a non-pharmacological therapy. This study sought to assess the impact of isometric handgrip exercise on blood pressure in hypertensive individuals in Tenajar Lor Village, Kertasemaya District, Indramayu Regency. This research design employs a quasi-experimental framework featuring a two-group pre- and post-test methodology alongside a control group design. The study sample comprised 30 respondents, categorized into intervention and control groups. The isometric handgrip exercise intervention was conducted daily for five successive days. The Wilcoxon test results indicated that the intervention group had an average systolic mean rank of 8.00 with a p-value of 0.000, and a diastolic mean rank of 7.50 with a p-value of 0.000. The control group exhibited a mean rank of 2.00 for systolic measurements with a p-value of 0.083, and a mean rank of 3.13 for diastolic measurements with a p-value of 0.157. The Mann-Whitney test yielded the average blood pressure disparity between the intervention and control groups. The p-values obtained were 0.001 for systolic blood pressure and 0.006 for diastolic blood pressure (p < 0.05). This study concludes that isometric handgrip exercise influences blood pressure in hypertensive patients. Individuals with hypertension are advised to perform isometric handgrip exercises autonomously at home. Healthcare professionals, particularly nurses, implement isometric handgrip exercises to regulate blood pressure in individuals with hypertension.